A Novel Approach Integrating Intuitionistic Fuzzy Analytical Hierarchy Process and Goal Programming for Chickpea Cultivar Selection under Stress Conditions - ŞENVAR, ÖZLEM; BULKAN, SEROL (MDPI, 2020)
Chickpea (Cicer arietinum L.) is a quite high nutrient and widespread legume that is consumed globally. Similar to many plants, chickpea is sensitive to environmental stresses. The major goal of the breeders is to achieve the most tolerant cultivars. This study aims to determine the tolerance level of chickpea cultivars against cold and drought stresses. The cultivars in the scope of this study are the ones that are officially identified and grown in Turkey. Ranking alternatives according to multiple criteria is difficult and requires a systematic approach. Thus, a coherent multi criteria decision making (MCDM) methodology is proposed in order to ease the ranking process. The methodology includes integration of intuitionistic fuzzy analytical hierarchy process (IF-AHP) with group decision making (GDM) and goal programming (GP). This integration presents a robust ranking according to criteria that are appraised by talented experts. Applying the methodology to the data, results in the order of chickpea cultivars with regard to their cumulative tolerance to cold and drought stresses. Diyar 95 spearheads this list with its utmost performance. The main contribution of this study is the proposition of the powerful MCDM approach with systematic procedure for the ranking process of cultivars. The proposed methodology has a generic structure that can be applied to various stress problems for different plants.
Keywords: chickpea; Cicer arietinum L; cold stress; drought stress; MCDM; intuitionistic fuzzy; IF-AHP; goal programming; CICER-ARIETINUM L.; DECISION-MAKING; SUPPLIER SELECTION; DROUGHT STRESS; COLD STRESS; TOLERANCE; YIELD